Tourism and the lodging sector - Timothy, Dallen J.; Teye, Victor B. (Butterworth-Heinemann/Elsevier, 2009)
Tourism and the Lodging Sector is a pioneering book and is the first text of its kind to examine the lodging sector from a tourism perspective. The book highlights the importance of the lodging sector in tourism as a major income generator and essential part of the travel experience. The book offers an international perspective on topics such as sustainability, security, economic development, technology and globalization. Tourism and the Lodging Sector critically examines a wide range of lodging establishments from an industry and social science perspective, drawing parallels and distinctions between the various types of accommodation, from campgrounds for the cost-conscious or adventurous outdoor traveler, to luxury, five-star resorts, and more innovative accommodation such as tree-house hotels and ecolodges. This is essential reading for students of tourism, this book is an indispensable guide, unprecedented in the field of tourism management. -- Provided by publisher.